2005
DOI: 10.1007/s00383-005-1487-5
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive jaundice in a child with pancreatic hemangioma

Abstract: We report the case of a 2-year-old boy who presented with obstructive jaundice by pancreatic hemangioma. In this case, a minimal operation for obstructive jaundice without resection of the tumor was performed. Three years after the operation, the pancreatic hemangioma almost disappeared. We discuss treatment of the pancreatic hemangioma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…PD was performed with diagnosis of panNET because the boy's parents refused FNA biopsy and insisted on surgery. So far, only 2 cases of obstructive jaundice caused by pancreatic head hemangioma has been reported [14,15] (aged 5 months and 2 years old respectively) and neither of the tumors were removed. According to it, PD or even operation is not the best choice for the boy although his parents were satis ed with his rapid recovery.…”
Section: Discussionmentioning
confidence: 99%
“…PD was performed with diagnosis of panNET because the boy's parents refused FNA biopsy and insisted on surgery. So far, only 2 cases of obstructive jaundice caused by pancreatic head hemangioma has been reported [14,15] (aged 5 months and 2 years old respectively) and neither of the tumors were removed. According to it, PD or even operation is not the best choice for the boy although his parents were satis ed with his rapid recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that among children with hemangiomatosis treated with corticosteroids, about one-third responded well, whereas one-third gained no benefit [ 5 ]. Although interferon-alpha was administered to severely ill patients, it caused severe side effects [ 14 ]. In recent years, anti-VEGF drugs [ 15 ], such as ranibizumab and bevacizumab, have been used clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Размеры образований, по данным литературы, варьируют от 30 мм до 20 см [2]. Поскольку чаще гемангиому выявляют в головке поджелудочной железы (66%) [18], она проявляет себя болью [11,14], а также клинической симптоматикой, связанной с механической желтухой [18,20], тошнотой [7,18], возможны желудочнокишечное кровотечение, рвота кровью, мелена [2,7,15,21]. При лабораторном исследовании возможно выявление анемии и тромбоцитопении [7,22].…”
Section: êëèíè÷åñêèå íàáëþäåíèÿunclassified
“…В дальнейшем проводили динамическое наблюдение. Через три года после операции гемангиома поджелудочной железы практически исчезла [20]. Аналогичной тактике при лечении пациента придерживались и другие авторы [9].…”
Section: êëèíè÷åñêèå íàáëþäåíèÿunclassified